2020
DOI: 10.1113/ep088697
|View full text |Cite
|
Sign up to set email alerts
|

Combination of curcumin with autologous transplantation of adult neural stem/progenitor cells leads to more efficient repair of damaged cerebral tissue of rat

Abstract: New Findings What is the central question of this study?Can the neuroprotective agent curcumin affect restorative action of neural stem/progenitor cells in the injured rat brain? What is the main finding and its importance?In the presence of curcumin, transplantation of neural stem/progenitor cells in the context of PuraMatrix reduced lesion size and reactive inflammatory responses, and boosted survival rate of grafted neurons. In addition it improved the neurological status of injured animals. This could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
(59 reference statements)
0
1
1
Order By: Relevance
“…However, there were no significant differences between the combined treatment group with stem cells and CM-NPs groups. Our results are in contrast to the expectations and earlier findings 44 , 45 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, there were no significant differences between the combined treatment group with stem cells and CM-NPs groups. Our results are in contrast to the expectations and earlier findings 44 , 45 .…”
Section: Discussioncontrasting
confidence: 99%
“…Further experimentation evaluating microglia activation at chronic stages will be required to fully assess the potential anti-inflammatory effect of the CURC containing scaffolds. A study on traumatic brain injury revealed that the transplantation of PM-embedded rat NPCs alone or in combination with free curcumin decreased microglial activation and macrophage infiltration when evaluated at one month after treatment [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%